2007
DOI: 10.1128/iai.00957-06
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Lipopolysaccharide-CD14 Complex for the Activity of Hemolysin from Uropathogenic Escherichia coli

Abstract: Bacterial pathogens produce a variety of exotoxins, which often become associated with the bacterial outer membrane component lipopolysaccharide (LPS) during their secretion. LPS is a potent proinflammatory mediator; however, it is not known whether LPS contributes to cell signaling induced by those microbial components to which it is attached. This is partly due to the common view that LPS present in bacterial component preparations is an experimental artifact. The Escherichia coli exotoxin hemolysin (Hly) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 52 publications
(61 reference statements)
2
24
0
Order By: Relevance
“…In addition, sublytic concentrations of HlyA have been recently found to potently stimulate the inactivation of the serine/threonine protein kinase B (PKB), which enzyme plays a central role in host cellcycle progression, metabolism, vesicular trafficking, survival, and inflammatory-signaling pathways . These findings may help to explain previously published results implicating sublytic concentrations of HlyA in the inhibition of chemotaxis and in bacterial killing by phagocytes in addition to the HlyA-mediated stimulation of host apoptotic and inflammatory pathways (Cavalieri & Snyder, 1982), (Koschinski et al, 2006), (Mansson et al, 2007), (Tran Van Nhieu et al,2004), (Uhlen et al, 2000).…”
Section: The Mechanism Of Action Of Hlyasupporting
confidence: 67%
“…In addition, sublytic concentrations of HlyA have been recently found to potently stimulate the inactivation of the serine/threonine protein kinase B (PKB), which enzyme plays a central role in host cellcycle progression, metabolism, vesicular trafficking, survival, and inflammatory-signaling pathways . These findings may help to explain previously published results implicating sublytic concentrations of HlyA in the inhibition of chemotaxis and in bacterial killing by phagocytes in addition to the HlyA-mediated stimulation of host apoptotic and inflammatory pathways (Cavalieri & Snyder, 1982), (Koschinski et al, 2006), (Mansson et al, 2007), (Tran Van Nhieu et al,2004), (Uhlen et al, 2000).…”
Section: The Mechanism Of Action Of Hlyasupporting
confidence: 67%
“…Specifically, the treatment of bladder cells with the K ϩ ionophore valinomycin (1-40 M for 2 h) did not alter the phosphorylation status of Akt and neither chelation of intracellular Ca 2ϩ pools nor the use of 5 mM KCl in the cell culture medium (to prevent K ϩ release during infection with UPEC) had any inhibitory effect on HlyAmediated dephosphorylation of Akt ( Figure 4B; unpublished data). Moreover, the mechanism by which HlyA induces Ca 2ϩ oscillations has recently been shown to be dependent on the small GTPase RhoA (Mansson et al, 2007a). By using a cell-permeable variant of the RhoA inhibitor C3 transferase (4 g/ml), which effectively inactivates RhoA in 5637 bladder cells, we again observed no abrogation of HlyA-mediated dephosphorylation of Akt (unpublished data).…”
Section: Discussionmentioning
confidence: 60%
“…Furthermore, we found that disruption of LPS (lipopolysaccharide) biosynthetic genes within the rfa and rfb operons, which were recently shown to contribute to UPEC-mediated suppression of host cytokine responses (Hunstad et al, 2005), did not prevent UTI89-mediated dephosphorylation of Akt ( Figure 2E). LPS promotes hemolysin interactions with host cells and mutations within the rfa operon, which affect the generation of the LPS core polysaccharide, result in decreased levels of hemolysin secretion (Bauer and Welch, 1997;Mansson et al, 2007a). Interestingly, in our experiments the rfa mutant was reproducibly less effective than wild-type UTI89 at inducing Akt dephosphorylation ( Figure 2E), possibly reflecting either decreased HlyA secretion by the rfa mutant and/or impaired LPS-modulated HlyA interactions with the target host cells.…”
mentioning
confidence: 99%
“…Interestingly, mutations in either TolC or HlyD also result in secreted HlyA with reduced hemolytic activity, suggesting a tight coupling between the secretion process and the folding of the exported protein [113,137]. Other studies have suggested a role of the outer membrane lipopolysaccharide (LPS) in the secretion, folding, and activity of several RTX toxins [138][139][140][141].…”
Section: Assembly Of the T1ss Apparatusmentioning
confidence: 99%